The development of a technique for the recording of the intrapartum fetal electroencephalogram – a feasibility trial. (16th November 2010) - Field, K; Korotchikova, I; O'Riordan, MN; Boylan, GB
Abstract : Background: Intrapartum fetal monitoring is a standard part of perinatal care, despite a lack of robust evidence that it reduces morbidity and mortality in low risk pregnancies. The main premise is that fetal cardiac changes are a proxy measure of potential neurological compromise. An alternative option is to directly examine fetal brain activity. This study aims to examine the feasibility of using the fetal electroencephalogram (EEG) to monitor intrapartum neurological activity. Methods: The fetal scalp electrode (FSE) was modified to enable it to record an EEG. This was initially tested on 10 adults. Five women were then enrolled in the study. Two FSEs were placed on the fetal scalp during labour and a signal tracing was collected. The signal was examined and the EEG output was then assessed. Results: The altered FSE successfully recorded an adult EEG in all 10 adults and was recognisable as an adult EEG. All five intrapartum fetal EEGs were recorded, interference from the fetal heart was evident in the recordings, a recognizable EEG was extracted. They were well tolerated. Conclusion: The authors have shown that intrapartum fetal EEG's are possible to record and that a recognizable trace achieved albeit with artefact. Once the reading is being reliably recorded the next step will be to correlate the recordings with clinical outcomes.